Penerapan Model Discovery Learning Untuk Meningkatkan Pemahaman Konsep Peserta Didik Pada Materi Organ Tumbuhan Kelas XI MIA SMA Negeri 2 Fatuleu Barat - Mery Uskono; Getrudis Nau; Nofri A. H. H. S. Natonis (JBIOEDRA: Jurnal Pendidikan Biologi, 2024)
The aim of this research is to see an increase in students' understanding of concepts using the Discovery Learning model for Class XI MIA SMA Negeri 2 Fatuleu Barat. This research is classroom action research, which consists of four components in each cycle, namely planning, action, observation and reflection. The subjects in this research were 23 class XI MIA students at SMA Negeri 2 Fatuleu Barat. The data analysis technique used is qualitative descriptive analysis and quantitative descriptive analysis. The research results show that the Discoveri Learning model can increase students' conceptual understanding in measuring student learning outcomes, where in cycle I the presentation of learning completeness only reached 91% with high completeness criteria, while in cycle II it increased to 100% with very high completeness criteria. From the analysis data, it is concluded that understanding of concepts in Biology subjects using the Discovery Learning model is very high.